A preliminary study of roselle extract as antibacterial towards staphylococcus epidermidis by disk diffusion method - Yaacob, Yanti; Mohd Zamri, Syasya Izzati; Tengku Kamarul Baharin, Tengku Qistina Aisyah; Rossaidi, Nur Alya Syifaa; Roslan, Rabi’atul Adawiyah; Ahamad Norddin, Nurul Syakirin (2025)
Roselle also known as Hibiscus sabdariffa, calyx extracts are frequently used in traditional folk medicine and could be useful in natural sources of antimicrobial activity. The calyces are developed with substances that have rich content of antimicrobial properties, antioxidants, and anthocyanins. This research aims to investigate the antibacterial properties of roselle extract towards Staphylococcus epidermidis and record inhibition zone produced by roselle extract towards S. epidermidis. This involved the disk diffusion method whereby sterile paper disks with various concentrations of roselle extract were inserted onto an agar plate strewn with S. epidermidis, and the inhibition zone was measured after incubating. Results showed that H. sabdariffa induced a significant zone of inhibition of 12 mm for roselle extract A and 11 mm roselle extract B against which is a duplicated sample against S. epidermidis in the disk diffusion method. Since this bacterium is a common cause of skin infections, the potential of roselle would be most beneficial in developing a skin preparation that would target bacterial growth with no harsh chemicals. This study has led to further investigations into the antimicrobial mechanisms of roselle since it could also be more beneficial in understanding how it interacts with bacterial cells for better clinical applications. The other way could be testing its effectiveness in the real medical and skin care environment, which would end in safer and more efficient natural products.